Best staged plans [large type] - Cook, Claire, 1955- (Thorndike Press large print core series., 2011)
A professional home stager in the Boston suburbs, Sandy Sullivan, after reading her family the riot act, takes a job staging a boutique hotel in Atlanta where she becomes immersed in other people's lives while trying to fix up her own.